Molecular Epidemiology of Penicillin-Nonsusceptible Streptococcus pneumoniae among Children in Greece - Bogaert, Debby (American Society for Microbiology, 2000)
A total of 145 penicillin-nonsusceptible Streptococcus pneumoniae strains were isolated from young carriers in Greece and analyzed by antibiotic susceptibility testing, serotyping, restriction fragment end labeling (RFEL), and penicillin-binding protein (PBP) genotyping. The serotypes 23A and 23F (54%), 19A and 19F (25%), 9V (5%), 15A, 15B, and 15C (4%), 6A and 6B (4%), and 21 (4%) were most prevalent in this collection. Fifty-three distinct RFEL types were identified. Sixteen different RFEL clusters, harboring 2 to 32 strains each, accounted for 82% of all strains. Eight of these genetic clusters representing 60% of the strains were previously identified in other countries. A predominant lineage of 66 strains (46%) harboring five RFEL types and the serotypes 19F and 23F was closely related to the pandemic clone Spain(23F)-1 (genetic relatedness of ≥85%). Another lineage, representing 11 strains, showed close genetic relatedness to the pandemic clone France(9V)-3. Another lineage of 8 serotype 21 strains was Greece specific since the RFEL types were not observed in an international collection of 193 genotypes from 16 different countries. Characterization of the PBP genes pbp1a, pbp2b, and pbp2x revealed 20 distinct PBP genotypes of which PBP type 1-1-1, initially observed in the pandemic clones 23F and 9V, was predominantly present in 11 RFEL types in this Greek collection of penicillin-nonsusceptible strains (55%). Sixteen PBP types covering 52 strains (36%) were Greece specific. This study underlines the strong contribution of penicillin-resistant international clones to the prevalence and spread of penicillin-nonsusceptible pneumococci among young children in Greece.